REDEFINING DEVELOPMENT POLICIES THROUGH RE-EXPORTS IN FIJI’S ECONOMY - Rettab, B; Azzam, A (Economics and Statistics Research Journal (ESRJ), 2022)
Abstract Re-exports play a significant role in international trading accounts and are recognized as vital to small island states’ total exports. Fiji is no exception as re-exports continue to dominate its trade, while domestic exports lack literature regarding performance. This study aims to investigate the potential of re-exports in Fiji and their contribution to total exports and trade growth. Using time series data from 1985 to 2018, an ARDL model was employed to establish a relationship between re-exports, domestic exports, and total exports. Diagnostic testing was performed, affirming the stability of the model, thereby allowing for hypothesis testing. The results showed that re-exports were a significant predictor of Fiji’s total exports and trade growth. The study contributes to the growing literature on trade policies emphasizing the importance of re-exports to total exports for small island states. It concludes by recommending that national policies promote re-exports and include them in trade statistics as they generate revenue and should not be neglected as their exclusion may distort an economy’s market share and sector competitiveness.